Review of research and development of accelerator-driven system in Japan for transmutation of long-lived nuclides - Mukaiyama, Takehiko; Takizuka, Takakazu; Mizumoto, Motoharu; Ikeda, Yujiro; Ogawa, Toru; Hasegawa, Akira; Takada, Hiroshi; Takano, Hideki (Progress in nuclear energy (New series), 2001)
Active and comprehensive studies on an accelerator-driven subcritical system (ADS) for transmutation of long-lived nuclides have been carried out at the Japan Atomic Energy Research Institute (JAERI). In the late 1970's, JAERI started the basic study of this subject and later, comprehensive studies have been performed under the “OMEGA” program of Japan: the long-term program for research and development on partitioning and transmutation (P&T) technology. Based on a design study of a dedicated transmutation system, JAERI decided to concentrate its efforts for transmutation study on the development of ADS. The construction of an experimental facility for the ADS development was proposed as a part of the Neutron Science Project of JAERI, which aimed at the construction of the world most powerful spallation neutron source. Since 1998, JAERI and the High Energy Accelerator Research Organization (KEK) are jointly proposing a High-Intensity Proton Accelerator Project. An ADS experimental facility composed of a subcritical assembly and a liquid lead-bismuth target/coolant engineering facility will be constructed under this project. In this paper, the development of ADS at JAERI, together with related technologies of P&T, both under the OMEGA program and the joint proposal, is reviewed. Other activities on ADS study in Japan are also reviewed.